ALTERNATIF KELEMBAGAAN KEMITRAAN BAGI PEMBERDAYAAN NELAYAN PERIKANAN TANGKAP DI KOTA AMBON - Yoisye Lopulalan (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
The availability of potential fishery resources owned by the waters around Ambon Island has not been fully supported by the ability of human resources to manage them properly. The mastery of technology and management in the field of fisheries and marine owned by coastal communities in Ambon is still limited to be able to utilize the potential of fisheries and marine resources available. On the other hand, the availability of capital to stimulate economic activities in the fisheries and marine sector has also not been fully met. The mastery of knowledge and business skills of the people living on the coast of Ambon is still traditional and subsistence in nature, so efforts are still needed to increase the productivity of businesses owned by the community. From the description of the conditions in the Ambon area, the presence of partnerships initiated by the government or the private sector is urgent in the framework of empowering fishing communities in this region. This study aims to formulate an alternative framework of partnership institutions that are appropriate for the empowerment of capture fishermen in Ambon. The research method used case study method, data collection using focus group discussion method. Data analysis uses a qualitative descriptive approach. The output of this research is an alternative framework of capture fisheries partnership institutions where in building a partnership concept that can accommodate the aspirations of the community, it is necessary to study the potential of the community itself, both human capital, natural capital, and social capital, coupled with a proper understanding of the problems faced by the fishing community itself, so that the partnership that is built is right on target, which in turn can provide adequate results.